Opening up innovation processes through contests in the food sector. Issue 6 (6th November 2017) - Massa, Silvia; Testa, Stefania
Abstract : Purpose: The purpose of this paper is to investigate how an adequate mix of technological, organisational and managerial tools might support Open Innovation (OI) processes achieved by contests in the food sector. Design/methodology/approach: The methodology of this paper is exploratory in nature. Data have been gathered about the 140 innovation contests launched by the best global food brands (2013 BusinessWeek/Interbrand Best Global Brands) over the last decade. Findings: The research highlights the main changes that have occurred over the last decade, showing that the choice of platform type for contest launches is often neglected or considered as an ancillary element. Indeed, it is a choice that embeds another set of technological, organisational and managerial tools that strongly influence the collaborative behaviour (and the participation itself) of partners throughout the innovation process. Research limitations/implications: Companies investigated in this paper consist exclusively of top brands in the sector. Future research should strive to obtain larger samples, develop a set of fine-grained hypotheses, and test them by using appropriate statistical techniques. Originality/value: This paper fills an inexplicable gap in academic literature due to the fact that food companies are those that mainly use contests in order to implement OI but they are scarcely researched regarding this issue.